The gender perspective as a political commitment in the social intervention of Social Work - Chacon-Gironza, Laura Sofía (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
This article analyzes the challenges and difficulties faced by Social Work professionals in their intervention process (mainly those related to the health sector) and proposes theoretical and practical elements that allow facing the neoliberal dynamics, through a critical look at the social reality.The study starts from the perspective of gender as a way to identify and analyze the misnamed "social problems" of the population in general, placing a greater emphasis on the case of women from Cali who are in situations of discrimination, oppression and violence. It analyzes the scope of social intervention in neoliberal logic, with greater emphasis on the health sector. It also addresses the academic training in Social Work, its progress and difficulties, at the Universidad del Valle. Finally, it demonstrated the importance of the gender perspective in the practice of the profession, concluding that they are essential theoretical-practical tools to understand and analyze the social context in order to advance critical analysis.